International accounting - Doupnik, Timothy S. (McGraw - Hill, 2007)
The Fourth Edition of International Accounting provides an overview of the broadly defined area of international accounting, but also focuses on the accounting issues related to international business activities and foreign operations. This edition also includes substantially updated coverage of the International Accounting Standards Board (IASB) and International Financial Reporting Standards (IFRS). The unique benefits of this textbook include its up-to-date coverage of relevant material, extensive numerical examples provided in most chapters, two chapters devoted to the application of International Financial Reporting Standards (IFRS), and coverage of nontraditional but important topics such as strategic accounting issues of multinational companies, international corporate governance, and corporate social responsibility reporting.